The Impact of Board of Directors’ Reforms on Audit Fees in Companies Listed on the Tehran Stock Exchange - Zamani, Maryam; Abdoli , Fatemeh; Zabihzadeh, Abdollah (Business, Marketing, and Finance Open, 2024)
The presence of a strong and efficient board of directors in companies strengthens the control environment. It can be expected that the auditor's assessment of audit risk and audit procedures will be reduced, leading to decreased audit costs. Therefore, the purpose of this study was to examine the impact of board of directors' reforms on audit fees. This study employed a descriptive, ex-post facto research method and is classified as applied research in terms of purpose. The statistical population included all active companies listed on the Tehran Stock Exchange during the years 2018 to 2022, totaling 603 companies. Using a systematic elimination method, a sample size of 180 companies was selected as a census sample. Data were collected from audited financial statements published on the Codal website, Rahavard Novin software, and the Securities and Exchange Organization website, and extracted using panel data methods. Data analysis was performed using regression tests with Excel and EViews software. The results of the study showed that board of directors' reforms do not affect audit fees, but company size has a significant impact on audit fees. Consequently, it can be concluded that there are other factors and variables influencing audit fees that require further investigation and research.